Finite element analysis of achilles tendon in jumping phase - Gu, Y.; Li, J.; Ren, X. J.; Lake, M. J. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The prevalence of Achilles tendon(AT) injury is high in various sports, but the tendon internal dynamic variation in the movement is not fully understood.Based on the CT scan and CAD/CAM software processing, the ankle three-dimensional model were created. Achilles tendon`s stress-strain change were acquired through finite element analysis of one-legged jumping. The largest stress was appeared in the push phase and concentrated in the 6 cm above the calcaneal insertion. This model can be applied to research the achilles tendon, and provide mechanics data in jumping trauma.